Handbook of research on advances in health informatics and electronic healthcare applications global adoption and impact of information communication technologies - Khoumbati, Khalil 1965-; Dwivedi, Yogesh K.; Srivastava, Aradhana; Lal, Banita (Medical Information Science Reference, 2010)
"This book presents a comprehensive resource elucidating the adoption and usage of health informatics" - Provided by publisher
Includes bibliographical references and index
Keywords: Betriebliches Informationssystem; Gesundheitsinformationssystem; E-Health; Aufsatzsammlung